A CRITICAL UNDERSTANDING OF ASHRAYA-ASHRAYI BHAVA (AYUSHDHARA, 2017)
Health is a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity. Any disturbance in the equilibrium in the Dhatus known as disease and on the other hand, the state of their equilibrium is health. Health and disease defined as pleasure and pain. Ayurveda based on the premise that the universe made up of five elements: air, fire, water, earth, and ether. These elements represented in humans by three "Doshas,” or energies: Vata, Pitta, and Kapha. Ayurveda aims at maintaining the health of the healthy persons and curing ailments of diseased, many of concepts explained in Ayurveda that serve these purposes. Both Physiological and pathological units depend upon the balance of Dosha, Dhatu and Mala. Ashraya Ashrayi Bhava is the unique concept in Ayurveda deals the interdependency of Dosha, Dhatu and Mala. This concept elucidated to distinguish the relation between the Dosha Dhatu, and Mala. Dosha, Dhatu and Mala are the main constituents of human body. Doshas are interpreted Gunatha, Karmatha and they are inherent in Dhatus and Mala to exhibit it qualities and functions. There is a wide range of application of the concept. Here these interpreted in physiological, pathological aspect, in development of disease, prognosis of disease and in planning appropriate treatment.